Direccionamiento estratégico de la Empresa Comercial Oruliaceros de la ciudad de Babahoyo. - Murillo Andaluz, Denis Alexi (2022)
The development of this work was carried out in the company Oruliaceros, which is consolidated in the local market of the city, began its activities in 1999, located at Av. Enrique Ponce Luque S/N and Tercera Transversal in the city of Babahoyo la which is dedicated to the retail sale of spare parts, components, consumables, mechanical spare parts and auto parts such as tires and tubes, including spark plugs, batteries, spare parts for lighting equipment and electrical parts. However, being a company in constant growth thanks to a great reception, the internal analysis shows that the company does not adequately manage talent management, and the existence of inefficient work performance. Bad work is scandalous and, consequently, an imminent decrease in the production of workers, which leads to negative changes in job performance. Therefore, given the previous context, the ability to provide a Comercial Oruliaceros company with a strategic management model is presented as a fundamental factor for better growth in a world in constant change, and at the same time, it is fundamental that companies appreciate the importance they deserve for their human capital, which is the backbone of any company, with the full and competitive development of their activities.